(untitled) (Bangladesh Journal of Agricultural Research, 2009)
Heterosis in bottle gourd was studied in a set of 13 F1 with 26 parents. Results indicated highly significant differences for all the characters among the materials studied. Heterosis was higher for yield per plant, number of fruits per plant and individual fruit weight, medium in fruit length and fruit diameter, and lower in days to 1st harvest. Hybrids (F1) 10 x 17 and 19 x 26 manifested highest heterosis over midparent (73.1%) and better parent (61.8%), respectively, for yield per plant. Key Words: Heterosis, bottle gourd, hybrid. DOI: 10.3329/bjar.v34i3.3973 Bangladesh J. Agril. Res. 34(3) : 465-472, September 2009